Assessing the thermal adaptability of tree provenances: an example using Eucalyptus tereticornis. Issue 4 (2nd October 2019) - Booth, T. H.
ABSTRACT: A 2017 paper intended to assist climate-change studies concluded that provenances of the widely distributed Eucalyptus tereticornis 'are not differentiated in their thermal responses' in terms of photosynthesis, respiration and growth. The aim here was to place this surprising result, based on a short-term (48-day) experiment with seedlings of just three provenances, into the broader context of several years' growth of provenances of the same species. To do this, a re-analysis of results from trials of 14 provenances of E. tereticornis was undertaken. These were grown for 3.5 or 5.0 years at four contrasting sites in southern China spanning mean annual temperatures (MAT) from 15.0°C to 23.5°C. The analysis described here compares MATs at climate-of-origin with volume growth. It demonstrates an approach that could easily be applied to provenance studies of other commercially important species. It makes use of the ready access to distributional and climatic data provided by a modern biodiversity database, the Atlas of Living Australia. Some of the provenances showed a surprising level of adaptability to climates markedly different to those of their origin. At the warmest site in China, however, the growth of the provenances was significantly related to the MAT at their climate-of-origin. It is concluded that researchers considering the likely impacts of climate change on tree species may find it useful to examine results from commercial provenance trials as well as from glasshouse experiments with seedlings.